PERANAN KEPALA SUKU MONI DALAM PELAKSANAAN PEMBANGUNAN INFRASTRUKTUR JALAN DI DISTRIK WANDAI KABUPATEN INTAN JAYA PROVINSI PAPUA). - BAGAU, JELIDA; Rompas, Wilson; Plangiten, Novva (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: As it is known that the Organization of Indigenous Peoples is one container to collectand bamboozle indigenous peoples so that the role of traditional leaders more directly in supportingthe wheels of government in the implementation of development and provide guidance to the publicas mandated. In Law No. 21 of 2001 on Special Autonomy for Papua Province. Containing organizeand manage their own household / own government. Chieftain, is not set in legislation, but in the Act.No. 21, 2001, Article 1 Paragraph 13 of the "Consultative Council of Kampung or called by any othername is a group of people who form a unity composed of various elements, in the village as well aselected and recognized by local residents to provide advice and consideration to local government.The purpose of this study was to determine the role of Chief Moni in the implementation of roadinfrastructure development in the District Wendai Intan Jaya district of Papua province. Researchusing qualitative methods. Informants in this study were 10 people employed several elements takenfrom the head of the district, members of the traditional council, village heads, chiefs, religious figure,and the common people. Collecting data with interview techniques; while the data analysis usinganalytical techniques interactive model of Miles and Hubernann.The results showed the role of chieftain Moni in the construction of road infrastructure is realizedin three aspects: a role in decision making, a role in providing information to the public, and a rolein encouraging and mobilizing community participation. Based on the results of these studiesconclude that the chief Moni has a significant role in the implementation of development in theDistrict of Intan Jaya district Wandai.Based on the Conclusions of the research results it is suggested that the government districts andvillages should always involve; the chiefs in decision-making, in providing information to the public,and to encourage and Mobilize community participation in the construction of road infrastructure inthe District Wandai.Keywords: Role of Chief Moni, Road Infrastructure Development.